Implementasi Model Direct Instruction terhadap Minat Belajar Siswa pada Pelajaran Seni Budaya dan Prakarya - Ninis Anisya; Ajeng Puspitasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is motivated by the low level of student interest in Arts, Culture, and Crafts at school. This low level of interest is evident in the lack of active student participation, low enthusiasm during learning activities, and minimal initiative in completing arts and crafts practical assignments. This condition requires teachers to select and implement an appropriate learning model, one that not only delivers material clearly but also stimulates motivation and is suited to the characteristics of the students. One of the chosen models is Direct Instruction. This model emphasizes the teacher's delivery of material in a structured, clear, and systematic manner, followed by examples, guidance, and directed practice. The purpose of this study was to determine the extent to which the application of the Direct Instruction model can increase student interest in Arts, Culture, and Crafts. This study used qualitative methods with observation, interview, and documentation techniques to collect data. Analysis was conducted using descriptive qualitative methods by reviewing all field findings. The results showed that the application of the Direct Instruction model significantly increased student interest in learning. Students became more active in asking questions, enthusiastically followed instructions, and demonstrated improved skills in arts and crafts practicals. In addition, student involvement in class discussions also increased, and they were more confident in presenting their work. In conclusion, the use of the Direct Instruction model can be an effective alternative learning strategy to increase student interest in learning, particularly in Arts, Culture, and Crafts. Teachers are advised to combine this model with other creative methods to optimize learning outcomes.